Xper computed tomography‐guided translumbar inferior vena cava catheterization for long‐term hemodialysis: A case report and literature review. Issue 1 (29th November 2021) - Bo, Xiying; Liu, Yawei; Liao, Huaqiang; Bian, Rongrong; Mei, Changlin; Yu, Shengqiang; Dong, Weihua; Mao, Zhiguo; Ye, Chaoyang; Dai, Bing
Abstract: Hemodialysis is the most widely used renal replacement therapy for end‐stage renal disease patients. Exhausted vascular access due to repeated indwelling central venous catheters is becoming a challenging clinical problem, which also contributes to reduced survival of the hemodialysis patients. Lack of conventional peripheral and central venous access mandates the use of alternative strategies. We present a case of translumbar dialysis catheter (TLDC) for long‐term hemodialysis in a patient with central venous occlusion refractory to conventional endovascular techniques. After a careful literature review, totally 10 cohort studies including 216 cases through TLDC were reported. The incidence of procedure‐related complications was very low. The catheter‐related infection rate of TLDC was comparable with overall tunneled cuffed catheters (TCCs) reported by clinical practice guidelines for vascular access. Although the patency might be relatively low due to the catheter‐related complications, TLDC could be rescued by multiple systemic and topical medications and interventional therapies. Percutaneous translumbar placement of a cuffed tunneled hemodialysis catheter directly into the inferior vena cava (IVC) can provide a relatively safe salvage when traditional central venous sites such as the internal jugular, femoral, subclavian veins are unavailable. Xper computed tomography together with real‐time fluoroscopic guidance can reduce the intraoperative risks and complications.